The study of Recoil Reducing Compact Air Pressure Device (CAPD). Issue 1 (March 2021) - Saxena, Abhimanyu; Dixit, M; Rashid, M; Nigam, S C; Singh, S K
Abstract: Defense organization is one of the most reputed organization where best of the officers and soldiers serve for the safety on one's country, without complaining about anything and giving their all in to protect us from various threats that could lead to disintegration of the country. Thus, the main motive to develop this device is to help our defense services to get the best, while they are giving their best for the country. The idea is to develop a device that would counter the recoil of the gun used by the officers and soldiers, to make them more efficient. Keeping in mind that the renewable resources of energy are depleting at a fast pace and pollution is increasing day by day leading to global warming, we have taken air as our resource to produce the desired effect. The device would be developed using aluminium, compact single cylinder air compressor and arduino programming to measure the pressure required for each shot fired from the gun. The principles of Law of conservation of momentum are applied to reduce the recoil of the gun to 80 %, thus helping in better aiming and precision. By installing this device, the demerits that makes AK47 a primitive gun would be subdued and without buying the expensive advanced guns, the arsenal would be upgraded at minimal cost possible.